(untitled) (शोधसुधा Shodh Sudha, 2025)
This research aims to explore the mental condition of the character of the story The Tell-Tale Heart of Edgar Allan Poe. The narrator of the story known as the principal character seems to be absolutely rational in the beginning of the story and he is over conscious of hiding the facts of his murdering the old man. He has attempted for seven nights and he murdered the old man on the eighth night. He disembarked the body into pieces and put under the planks and he has made even the police officer believe that he is out of guilt and it is his acute hearing capacity has turned his rationality into irrationality and thinking that the police officers have been mocking him and he has opened the facts of his crime by confessing the murder of the old man. The research has been carried out with the detail analysis of the primary data of the story The Tell-Tale Heart and the various related articles have been used as the secondary data of the research. Freudian psychological theory has become analogue through the lance of analyzing it.